Specificities of multi-primer polymerase chain reaction optimization for the detection of infectious pneumonia agents in human - E. S. Klochikhina; V. E. Shershov; V. E. Kuznetsova; S. A. Lapa; A. V. Chudinov (Тонкие химические технологии, 2021)
Objectives. The objectives of this work are the development of a multi-primer system based on the polymerase chain reaction (PCR) aimed at the simultaneous detection of six bacterial pathogens that cause human pneumonia and the determination of the parameters important for the optimization of this multi-primer system, including solid-phase PCR systems (biological microarrays).Methods. To determine the optimal parameters of the system, PCR methods were used in monoplex and multiplex formats.Results. Primers for Staphylococcus aureus, Pseudomonas aeruginosa, Haemophilus influenza, Legionella pneumophila, Klebsiella pneumoniae, and Streptococcus pneumoniae detection were designed, and the PCR cycling conditions were optimized. The patterns of primer design for solidphase PCR were revealed.Conclusions. The developed prototype of a system specifically identifies six clinically significant bacterial pathogens. It could be expanded for the analysis of viral and fungal pathogens and used in clinical diagnostics. A prototype of a system for pathogenic agent detection in the immobilized phase (biological microarray) was created.